Faktor-Faktor Yang Mempengaruhi Konsultan Untuk Dapat Mengikuti Tender: Studi Kasus Tender Proyek di LPSE Jakarta - Abdul Aziz (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Tendering or procurement process is one of the common ways used by government agencies and private companies in obtaining consultant services for certain projects. In the tender process, consultants are expected to submit competitive bids and in accordance with project needs. Therefore, the factors that influence consultants to be able to participate in tenders are important to understand. This abstract aims to identify and analyze the factors that influence consultants to be able to participate in tenders. This research was conducted through literature review and questionnaire with consultants who are experienced in following the tender process. Some of the factors identified, By understanding the factors that influence consultants to be able to participate in tenders, the party holding the tender and the consultant himself can make the right preparations and strategies to increase the chances of success in the tender process. In addition, this research also contributes to improving understanding of the dynamics of the consultant market and the procurement of consulting services in the context of tenders.